Pleocnemia siamensis (Dryopteridaceae), a new fern species from southern Thailand - Xu, Xiao-Gang; Zhang, Li-Bing (Phytotaxa, 2016)
A new fern species, Pleocnemia siamensis (Dryopteridaceae), is described and illustrated from Yala Province, southern Thailand. Pleocnemia siamensis is most similar to P. macrodonta in the dissection of laminae and morphology of sinuses, but the former has sori in one row on each side of the costules and located at the ends of the veinlets (rarely on the back of the veinlets), while the latter has sori in two rows on each side of the costules and located on the back of veinlets. Pleocnemia siamensis is described from limestone cliffs in a national park and is classified as CR-critically endangered IUCN category.